Issues in contemporary Islamic housing - Spahic, Omer (International Islamic University Malaysia, 2015)
This paper discusses the subject of Islamic housing and some major requirements for its revival today. The following thrusts are the focus of the paper: 1) The meaning of Islamic housing; 2) Sound housing policies; 3) Avoiding major transgressions associated with housing; 4) Endless creativity and Islamic housing: 5) Some practical suggestions for planning and designing Islamic houses. The paper concludes that Islam as a comprehensive way of life influenced greatly the planning and designing of the houses of its adherents. Not only that, Islam also laid a solid foundation, in some instances in form of laws, for creating what became known as the phenomenon of Islamic housing. In Islam, the house is an institution. It occupies an important position. It is a family development center. It is a microcosm of Islamic culture and civilization. The character of the paper is conceptual rather than empirical.